GENERASI X, Y, Z: SIAPA YANG PALING BAHAGIA DI KARAWANG? - Nita Rohayati; Lania Muharsih; Linda Mora (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2024)
This study aims to analyze the level of happiness and well-being among three generations, namely Generation X, Y, and Z, in Karawang Regency. The method used is a quantitative survey with the PERMA Profiler instrument to measure the dimensions of well-being based on five main factors: positive emotions, engagement, relationships, meaning, and achievement. The sample of this study consisted of 300 respondents, with 100 respondents each for Generation X, Y, and Z. The results of statistical analysis using ANOVA showed that there was no statistically significant difference in well-being scores between the three generations (p = 0.45). Although Generation X had the highest well-being score, the difference was not large enough to be considered significant. The discussion shows that although there are differences in the average well-being scores, these three generations generally have relatively good well-being and are in the normal function category. The implication is that even though there are no significant differences, policies are still needed that focus more on improving well-being, especially among the younger generation, in terms of mental health, stress management, and healthier social relationships. Penelitian ini bertujuan untuk menganalisis tingkat kebahagiaan dan kesejahteraan di antara tiga generasi, yaitu Generasi X, Y, dan Z, di Kabupaten Karawang. Metode yang digunakan adalah survei kuantitatif dengan instrumen PERMA Profiler untuk mengukur dimensi kesejahteraan berdasarkan lima faktor utama: emosi positif, keterlibatan, hubungan, makna, dan pencapaian. Sampel penelitian ini terdiri dari 300 responden, dengan 100 responden masing-masing untuk Generasi X, Y, dan Z. Hasil analisis statistik menggunakan ANOVA menunjukkan bahwa tidak ada perbedaan signifikan secara statistik dalam skor kesejahteraan antara ketiga generasi (p = 0,45). Meskipun Generasi X memiliki skor kesejahteraan tertinggi, perbedaan yang ada tidak cukup besar untuk dianggap signifikan. Pembahasan menunjukkan bahwa meskipun terdapat perbedaan rata-rata skor kesejahteraan, ketiga generasi ini secara umum memiliki kesejahteraan yang relatif baik dan berada dalam kategori fungsi normal. Implikasinya, meskipun tidak ada perbedaan signifikan, tetap diperlukan kebijakan yang lebih fokus pada peningkatan kesejahteraan, terutama di kalangan generasi muda, dalam hal kesehatan mental, pengelolaan stres, dan hubungan sosial yang lebih sehat.